Geolingvistična predstavitev izbranih frazemov s sestavino roka v slovenskih narečjih - Smole, Vera (Slavistična revija, 2008)
Phrasemes as units in the speaker's mental glossary have, from geographical point of view, similarly to lexical items, their areals in dialects, in which they exist in the same or different menanings and morphosyntactic structures. The author aims to demonstrate this on ten linguistic maps with commentary, i.e., on the example of selected phrasemes with the component roka 'hand', collected in 32 Slovene locations (two from outside of the borders of Republic of Slovenia) in various dialectal areas. She also compares the exsistence of these phrasemes in two social variants of Slovene and in other (particularly Slavic and contiguos) languages (and dialects).
Keywords: frazemi; frazeologija; geolingvistika; slovenska narečja; slovenščina